Entrepreneurs and cooperative values in the info-communication age - Vargas Sánchez, Alfonso (Revista Científica Visión de Futuro, 2004)
Social economy forms of organization, with cooperatives as their main exponent, are playing an increasingly active and prominent part in today's society, in which the development of entrepreneurial ability has become one of the priorities of employment policies, so much so that the creation of firms has even been described as eighth art. The businessman is currently identified with the entrepreneur, and in cases where the latter is a corporate body it finds in cooperatives a formula with a very particular profile that chimes in with certain ruling values of our society. No firm can be detached from the feelings, wishes and hopes of the society of which it forms part, on the contrary it needs to interiorise those values and align its behavior with them if it is to provide its "stakeholders" with exactly what they are looking for. This is a specific strength of the culture of cooperativism, which is steeped in democracy, solidarity etc. without conflicting with the business management efficiency that makes its survival and development possible.